بعض أساليب المعاملة الوالدية وعلاقتها باضطرابات النوم لدي عينة من رياض الأطفال بالمملكة العربية السعودية - القحطاني, د. حنان مبارك محمد (Sulaimani Journal for Humanities, 2021)
The aim of the research is to uncover some styles of parental treatment and their relationship to sleep disorders in a sample of kindergartens in the Kingdom of Saudi Arabia, the strength of which reached (219) children, and after applying the research tool represented in the Parental Treatment Styles Scale prepared by Abdel Naim Arafa (2019), and the scale Sleep disturbances prepared by the researcher, The most important results showed the existence of a statistically significant p positive relationship between the authoritarian style (the image of the father, the image of the mother) as one of the styles of parental treatment and sleep disturbances, and a negative relationship of statistical significance was found between the consultative style (the image of the father, the image of the mother) as one of the styles of parental treatment and sleep disorders, While there was no statistically significant relationship between the permissive style as one of the parental treatment styles and sleep disturbances, the results also indicated that sleep disturbances can be predicted through some parental treatment styles, and the results also showed that the authoritarian style (the father's image) as one of the parental treatment styles is more The studied variables contributed to sleep disorders, while the authoritarian and permissive style (mother's image) as one of the parental treatment styles was the most studied variable contributing to sleep disorders.
Keywords: styles parenting; sleep disturbances; kindergarten